Turbulence measurements in a Short Take-Off Vertical-Landing fountain - Saddington, Alistair J.; Knowles, Kevin (AIAA, 2013)
THE wall jets created by the impingement on the ground of the individual jet flows from a jet-lift short take-off and vertical landing (STOVL) aircraft with two nozzles meet at a stagnation line and form an upward-flowing fountain that interacts with the airframe (Fig. 1). While it is evident that the fountain upwash flow is unsteady, only limited data on the transient characteristics of this flow region are available. Early experiments relied on intrusive measurement techniques to provide mean pressure data [1] with unsteady pressures on the ground plane being used to infer additional information [2]. Direct measurement of turbulence data has been made using hot-wire anemometry [3,4], however, this technique is limited to low flow speeds and low turbulence intensities and is, therefore, likely to be inaccurate for compressible and highly unsteady flows; there is also the issue of probe interference. Techniques such as particle image velocimetry (PIV) and laser Doppler velocimetry (LDV) offer the possibility of detailed nonintrusive measurements in the fountain region. Recently, we have reported on the mean impinging-jet and fountain-velocity profiles obtained using PIV and LDV [5-7]. This paper extends the work further by presenting PIV-derived fountain turbulence characteristics.